4 - Entreprises étrangères et activités industrielles en Afrique de l’Ouest: by Amadou Kaka - Amadou Kaka (Africa Development, 1993)
In the context of industrialization projects, since independence African States have devised various investment policies aimed at attracting foreign investors. The major advantages offered have been focal incentives. Foreign investors adopt both defensive and offensive strategies when considering the establishment of enterprises outside their country. A case study of some African branches of French enterprises indicates that the role of fiscal incentives in the decision-making process of enterprises considering the establishment of industr 'uil activity in foreign countries is very limited, investors require sufficient guarantees and an overall environment which ensures the operation of an enterprise. The significant variables which shape the attitude of the investor include demand stability and the risk factor. But the likely political risk is a key parameter in the decision to create new branches and/or to keep existing ones operating. The current economic financial and social crises facing Africa and the anticipated potential of the East European market are factors which influence foreign investors. Can the process of democratization in Africa today create a climate which would encourage foreign investors to participate in the economic revival of African countries?